Analisis Pengaruh Ukuran Perusahaan dan Opini Audit Terhadap Audit Delay pada Perusahaan Sektor Properti dan Real Estate Yang Terdaftar di Bursa Efek Indonesia - Ameraldo, Fedi; Khoirunnisa, Ledhy (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This research aims to analyze and examine the effect of company size and audit opinion on audit delay in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) in the period 2017-2019. The population in this research is property and real estate sector listed on the Indonesia Stock Exchange (IDX) in 2017-2019. The purposive sampling method was used as a sample selection technique in the research. The sample that has been obtained is 44 property and real estate sector companies that are listed on the IDX and have annual financial reports that have been audited during 2017 - 2019. The data in this research were analyzed using logistic regression tests with SPSS software. The results of the wald test (partial t) in this research indicate that partially the firm size variable has no effect on audit delay, while the audit opinion variable has a positive effect on audit delay. Based on the results of the coefficient of determination (Nagelkerke's R Square) in this research, 58% of the independent variables were able to explain the variability of the dependent variable in the research, while 42% was influenced by other variables not examined in this study.